2017
DOI: 10.1155/2017/8434697
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Complementary and Alternative Medicine Use among Patients with Lung Cancer: A Cross‐Sectional Study in Beirut, Lebanon

Abstract: Patients with lung cancer are increasingly seeking complementary and alternative medicine (CAM) to improve their physiological and psychological well-being. This study aimed to assess CAM use among lung cancer patients in Lebanon. Using a cross-sectional design, 150 lung cancer patients attending the Basile Cancer Institute at the American University of Beirut Medical Center were interviewed. Participants completed a questionnaire addressing sociodemographic characteristics, lung cancer condition, and use of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
1
20
3
1
Order By: Relevance
“…3 Research has shown that complementary and integrative medicine (CIM) use among lung cancer patients ranges between 20-40%. 4 , 5 , 6 , 7 Complementary medicine is defined as a non-mainstream practice or procedure that is not part of standard medical care, used in combination with conventional medicine. Integrative medicine is defined as conventional and complementary approaches brought together in a coordinated way to treat the patient holistically.…”
Section: Introductionmentioning
confidence: 99%
“…3 Research has shown that complementary and integrative medicine (CIM) use among lung cancer patients ranges between 20-40%. 4 , 5 , 6 , 7 Complementary medicine is defined as a non-mainstream practice or procedure that is not part of standard medical care, used in combination with conventional medicine. Integrative medicine is defined as conventional and complementary approaches brought together in a coordinated way to treat the patient holistically.…”
Section: Introductionmentioning
confidence: 99%
“…About one-third of Lebanese adults (29.87%) were reported to use CAM in 2015, with the most prevalent being CAM products, specifically herbal supplements 7. Higher rates of use were reported among patients with chronic diseases such as infertility (41%),27 lung cancer (41%),28 and HIV and AIDS conditions (46.6%) 29. A common finding to most of the aforementioned studies was the low rate of disclosure to the treating physicians 7 26 28 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of use were reported among patients with chronic diseases such as infertility (41%),27 lung cancer (41%),28 and HIV and AIDS conditions (46.6%) 29. A common finding to most of the aforementioned studies was the low rate of disclosure to the treating physicians 7 26 28 30–32. This raised concerns about CAM safety, efficacy and impact on the patient health, especially when its use is coupled with poor regulatory frameworks 26…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Therefore, cancer patients may tend to choose alternative treatment that is considered cheaper and has no side effects, as stated in the study of Naja et al Naja et al are also stated that the prevalence of alternative medicine users among lung cancer patients is 41%, with the most commonly used modality is dietary supplements, and herbal remedies. 10 In this regard, the study about potential anticancer from the herbs is widely conducted by many researchers.…”
Section: Introductionmentioning
confidence: 99%